Evaluation of general practitioners’ routine assessment of patients with diabetes in Tshwane, South Africa - K.G. Leslie; L. Nkombua (South African Family Practice)
Background: Diabetes mellitus is a composite disease that, if not well managed and controlled, may lead to severe complications. To avoid or delay these debilitating complications, it is necessary for the practitioner to implement adequate management of the disease by using currently available clinical guidelines. The authors wished to establish the use of existing diabetes management guidelines by general practitioners (GPs) in the City of Tshwane (Pretoria) Metropolitan Municipality of South Africa.